2020
DOI: 10.1038/s41598-020-76844-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and within-host interaction of Theileria lestoquardi and T. ovis among naive sheep in Oman

Abstract: Mixed species infections of Theileria spp. are common in nature. Experimental and epidemiological data suggest that mixed species infections elicit cross-immunity that can modulate pathogenicity and disease burden at the population level. The present study examined within-host interactions, over a period of 13 months during natural infections with two Theileria spp., pathogenic (T. lestoquardi) and non-pathogenic (T. ovis), amongst a cohort of naive sheep in Oman. In the first two months after exposure to infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 26 publications
6
9
0
Order By: Relevance
“…The lower T. lestoquardi parasitemia in mixed infection is indicative of immune pressure (potentially innate in nature), which is expected to impact both parasites (T. lestoquardi and T. ovis). The above ndings are in line with our most recent data, in a cohort study of indigenous sheep in Oman, which revealed a signi cantly higher T. lestoquardi density in single infection vs mixed infection [7].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The lower T. lestoquardi parasitemia in mixed infection is indicative of immune pressure (potentially innate in nature), which is expected to impact both parasites (T. lestoquardi and T. ovis). The above ndings are in line with our most recent data, in a cohort study of indigenous sheep in Oman, which revealed a signi cantly higher T. lestoquardi density in single infection vs mixed infection [7].…”
Section: Discussionsupporting
confidence: 92%
“…(T. mutans and T. velifera) has been demonstrated in indigenous African Bos indicus calves [11]. This is consistent with our most recent work in Oman that linked mixed infection (T. lestoquradi plus T. ovis) to signi cant reduction of mortality among local breeds of sheep [7]. The present study extended these earlier ndings and examined clinical and hematological indices in sheep carrying mixed (T. lestoquradi plus T. ovis) compared to single species of T. lestoquardi.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations